The Personality Structure Of The Main Character In The Novel Aku Tak Membenci Hujan By Sri Puji Hartini: A Psychoanalytic Approach - Reza Arianggara (Applied Linguistics: Innovative Approaches and Emerging Trends, 2025)
This study describes the main character's personality structure in Sri Puji Hartini's novel Aku Tak Membenci Hujan, based on Sigmund Freud’s psychoanalytic theory including id, ego, and superego. Driven by the character's trauma-induced inner conflicts, this qualitative descriptive study analyzes textual quotations comprising words, sentences, and dialogues gathered via reading and note-taking techniques. Results show that Karang Samudra Daneswara’s personality is dominated by the id, manifested through emotional outbursts and instinctive drives when facing various conflicts. The ego balances these impulses with reality, while the superego provides moral considerations and deep guilt. This intense id dominance stems from childhood trauma and severe affection deprivation, shaping an emotional character filled with ongoing psychological battles. Ultimately, the novel effectively portrays human psychological complexity through the main character's inner struggles, proving how past experiences heavily distort an individual's current mental development and behavior.